2017
DOI: 10.1002/ecm.1247
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and predicting physiological performance of organisms in fluctuating and multifactorial environments

Abstract: International audienceUnderstanding how variance in environmental factors affects physiological performance , population growth, and persistence is central in ecology. Despite recent interest in the effects of variance in single biological drivers, such as temperature, we have lacked a comprehensive framework for predicting how the variances and covariances between multiple environmental factors will affect physiological rates. Here, we integrate current theory on variance effects with co-limitation theory int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 80 publications
(205 reference statements)
1
89
0
Order By: Relevance
“…Numerous studies have indicated the effect of these factors, but few consider them simultaneously (Couret, ; Couret & Benedict, ). Large‐scale experiments would be required to quantify the effect of interacting factors on insect development rate, together with more complex models taking into account the fluctuating and multifactorial environment experienced by insects (Régnière et al., ; Crespo‐Pérez et al., ; Koussoroplis et al., ). An additional layer of complexity is the integration of trophic interactions and phenological synchrony (e.g., with host plants), of particular importance for accurate model predictions in a context of climate change (Mwalusepo et al., ).…”
Section: Recent Advances and Future Directionsmentioning
confidence: 99%
“…Numerous studies have indicated the effect of these factors, but few consider them simultaneously (Couret, ; Couret & Benedict, ). Large‐scale experiments would be required to quantify the effect of interacting factors on insect development rate, together with more complex models taking into account the fluctuating and multifactorial environment experienced by insects (Régnière et al., ; Crespo‐Pérez et al., ; Koussoroplis et al., ). An additional layer of complexity is the integration of trophic interactions and phenological synchrony (e.g., with host plants), of particular importance for accurate model predictions in a context of climate change (Mwalusepo et al., ).…”
Section: Recent Advances and Future Directionsmentioning
confidence: 99%
“…For example, ecological physiologists and evolutionary biologists have innovatively incorporated the effects of Jensen's inequality into their efforts to model how plants and animals will respond to future changes in Earth's climate (e.g. Ruel and Ayres, 1999;Martin and Huey, 2008;Dillon et al, 2010;Williams et al, 2012;Vasseur et al, 2014;Colinet et al, 2015;Kingsolver et al, 2015;Dowd et al, 2015;Dillon and Woods, 2016;Koussoropolis et al, 2017). By contrast, biologists in other fields are often unaware of the quirks of nonlinear averaging.…”
Section: Introductionmentioning
confidence: 99%
“…In a thermally fluctuating environment, such changes of the TRN imply that the effect size of thermal variance might strongly depend on the nutritional context (Koussoroplis et al. ; Fig. ), a prediction that remains to be verified.…”
Section: Introductionmentioning
confidence: 99%